INFLUENCE OF FAMILY MONITORING AND SEXUAL COMMUNICATION IN ADOLESCENT CYBERSEX BEHAVIOR - Astrida Budiarti; Anisa Pujianti; Chabibah Chabibah; Dwi Ernawati (INTERNATIONAL JOURNAL OF NURSING AND MIDWIFERY SCIENCE (IJNMS), 2023)
Cybersex is the activity of accessing pornography on the internet, engaging in real-time, like conversations about online sexuality with others. The purpose of this study was to analyze the influence of family monitoring and sexual communication adolescent cybersex behavior in Sidoarjo. The study used cross-sectional analytics. Probability sampling technique with simple random sampling. Samples were 121 adolescent students of SMK Antartika 2 Sidoarjo. The research instrument used sexual communication questionnaires, family monitoring, and ISST questionnaires to assess cybersex behavior. Statistic test using rho sperman test. Results showed adolescent sexual communication with parents was 56.2% in the low, 29.8% moderate and 14% high categories. Family monitoring related to sexual behavior was 39.7% in the low category, 33.1% in the medium category, and 27.2% in the high category. Teen cybersex behavior was 61.9% riskless, 17.4% were low-risk, and 20.7% had high-risk behavior. The results of the spearman rho test between sexual communication and cybersex behavior showed p value = 0.000 which means that there is a relationship between sexual communication and cybersex behavior. In the family monitoring variable with cybersex behavior, it is obtained p value = 0.000, meaning that there is a relationship between family monitoring and adolescent cybersex behavior. It is hoped that families will pay more attention to adolescents in monitoring their sexual behavior. In addition, it also implements open communication with adolescents regarding their sexual behavior, so that adolescents avoid cybersex behavior.